The regulatory framework for credit inquiry and rating companies - abdulhussen Salem, Researcher. Habyab; Abdulbaqi Yousifa, Assist. Prof. Itidal (Basra studies journal, 2024)
The purpose of inquiry and credit rating is to achieve economic stability, and this cannot be achieved except by establishing an integrated legal regulation characterized by accuracy and clarity. The legislator has established legal texts that regulate these companies, regardless of their type, whether they are interconnected or independent companies, as specified Its obligations and the consequences of breach of these obligations. The credit inquiry and classification process may be practiced by banks as a banking service provided within the work that banks are obligated to carry out, or it may be a commercial work Among the commercial businesses practiced by commercial companies for the purpose of profit, the performance of these companies requires them to perform specific obligations that may be imposed by law or may be determined according to the terms of the agreement between the client and the company when concluding an inquiry or classification contract, and the consequences of breaching these obligations varied by The company, whether it is organized under special legal rules or left to be dealt with by general rules.